Synthesis of Anionic Surface Active Agents Containing Heterocyclic Moiety From Long Chain Fatty Alcohols - Abdellattif, Magda.H.; Eissa, A.M.F.; Mohamed, H.M. (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
A series of novel groups of anionic surface active agent were synthesized. Synthesis of these surfactants via the reaction of long chain fatty alcohols (octyl, decyl and dodecyl) with maleic anhydride to give monoester. The monoester chloride reacted with amino derivatives of heterocyclic rings followed by addition of NaHSO3 .The surface tension, interfacial tension; Kraft point, emulsifying and wetting power were evaluated. Stability to hydrolysis, biodegradability and biological activities were measured. A comparison studies between the chemical structures and the results were done.